2014
DOI: 10.1007/s00403-014-1495-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of obesity on the efficacy of ustekinumab in Japanese patients with psoriasis: a retrospective cohort study of 111 patients

Abstract: Obesity is thought to be involved in the pathogenesis of psoriasis, although its impact on the therapeutic response to systemic treatments remains unclear. The aim of this study was to examine the association of body mass index (BMI) with the efficacy of ustekinumab in Japanese patients with psoriasis. Clinical data from a cohort of 111 Japanese patients treated with ustekinumab 45 mg between July 2011 and March 2014 were retrospectively evaluated. The measured outcome was improvement in the psoriasis area and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 23 publications
3
15
1
2
Order By: Relevance
“…S1; see Supporting Information). In the screening stage, we initially genotyped 18 common variants of 14 psoriasis susceptibility genes ( LCE3D , IL12B , NFKB1A , TNIP1 , ERAP1 , ZNF683 , MTHFR , AIM2 , PTTG1 , GJB2 , SYNE2 , IKZF3 , SERPINB8 , ZNF816A ) and HLA‐Cw6 status in 90 patients with psoriasis . All these variants had been significantly associated with psoriasis in populations of Han Chinese descent at a genome‐wide level ( P < 5 × 10 −8 ) and met the following quality criteria: (i) minor allele frequency higher than 5% in both cases and controls and (ii) Hardy–Weinberg equilibrium in cases and controls with P > 0·0001.…”
Section: Methodssupporting
confidence: 90%
See 2 more Smart Citations
“…S1; see Supporting Information). In the screening stage, we initially genotyped 18 common variants of 14 psoriasis susceptibility genes ( LCE3D , IL12B , NFKB1A , TNIP1 , ERAP1 , ZNF683 , MTHFR , AIM2 , PTTG1 , GJB2 , SYNE2 , IKZF3 , SERPINB8 , ZNF816A ) and HLA‐Cw6 status in 90 patients with psoriasis . All these variants had been significantly associated with psoriasis in populations of Han Chinese descent at a genome‐wide level ( P < 5 × 10 −8 ) and met the following quality criteria: (i) minor allele frequency higher than 5% in both cases and controls and (ii) Hardy–Weinberg equilibrium in cases and controls with P > 0·0001.…”
Section: Methodssupporting
confidence: 90%
“…Patients with higher BMI require a higher dosage and faster dose escalation than that used in our study. A previous study showed that patients with BMI ≥ 25 had a significantly lower percentage reduction in PASI than those with BMI < 25 at week 16 . The study by Umezawa et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to bringing overall cardiovascular and metabolic benefits, weight loss may increase the effectiveness of psoriasis treatments. For example, ustekinumab treatment was found to be less effective in patients with higher BMI . FPG remained stable in the overall population and showed a trend towards a decrease in the diabetic population.…”
Section: Discussionmentioning
confidence: 97%
“…However, only a few studies have focused on clinical factors that may predict the efficacy of ustekinumab on treatment outcomes. Previous studies have shown that high bodyweight, high BMI, longer disease duration, psoriatic arthritis (PsA) and prior use of biologic treatments are associated with lower rates of response to ustekinumab. In several studies evaluating the efficacy of biologics, poor response to biologic agents was most strongly associated with high BMI/bodyweight .…”
Section: Discussionmentioning
confidence: 99%